2014
DOI: 10.5713/ajas.2013.13559
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Acetate Modulate Cytoplasmic Leptin in Bovine Preadipocytes

Abstract: Hormonal and nutrient signals regulate leptin synthesis and secretion. In rodents, leptin is stored in cytosolic pools of adipocytes. However, not much information is available regarding the regulation of intracellular leptin in ruminants. Recently, we demonstrated that leptin mRNA was expressed in bovine intramuscular preadipocyte cells (BIP cells) and that a cytoplasmic leptin pool may be present in preadipocytes. In the present study, we investigated the expression of cytoplasmic leptin protein in BIP cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…45,[54][55][56][57]59 One study found that butyrate can stimulate leptin expression in bovine pituitary cells but inhibits its expression in rat pituitary cells. 58 The remaining in vitro study found no statistically significant effect of acetate or propionate on leptin production, even though SCFA did activate FFAR2. 60 The mechanisms by which SCFA increase leptin expression were studied in vitro in five studies.…”
Section: In Vitro Studiesmentioning
confidence: 86%
“…45,[54][55][56][57]59 One study found that butyrate can stimulate leptin expression in bovine pituitary cells but inhibits its expression in rat pituitary cells. 58 The remaining in vitro study found no statistically significant effect of acetate or propionate on leptin production, even though SCFA did activate FFAR2. 60 The mechanisms by which SCFA increase leptin expression were studied in vitro in five studies.…”
Section: In Vitro Studiesmentioning
confidence: 86%
“…The capacity of lipid synthesis in adipocytes of ruminants is high compared to that in other species. Excess energy is stored as triglycerol, which is broken down into glycerol and fatty acids ( Yonekura et al, 2014 ; Choi et al, 2015 ). Fatty acids are consumed as an energy source in the peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%